Optimization of Counseling Guidance in Preventing Drug Abuse During the Covid-19 Pandemic by the Padangsidimpuan Police Binmas Unit - Randy Tri Yanda (Indonesian Journal of Police Studies, 2021)
This research is motivated by an increase in criminal acts of drug abuse in the jurisdiction of the Padangsidimpuan Police. Preemptive efforts are the most appropriate action to solve this problem, namely by relying on the role of counseling guidance carried out by Satbinmas. The purpose of this study was to determine the optimization of counseling guidance in preventing drug abuse during the COVID-19 pandemic by the Padangsidimpuan Police Binmas Unit. To process the data, this research uses interpersonal communication theory and counseling guidance management theory. This study uses a qualitative approach. The type of research is descriptive analysis. Data collection techniques with Interview, Observation, and Document Review. Data validity uses data triangulation. The results of the study found that the high level of drug abuse in the jurisdiction of the Padangsidimpuan Resort Police was caused by a lack of awareness from the public about the dangers of drugs. In addition, the public is still not open to the police regarding this case. It was concluded that the optimization of binluh in preventing drug abuse was not optimal. The suggestion put forward is to increase binluh by utilizing technology in the form of using virtual applications, especially during the covid 19 pandemic, as well as fulfilling facilities and infrastructure, improving the quality of Satbinmas personnel.